2014
DOI: 10.14573/altex.1311151
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of the REACH testing proposals system to reduce animal testing

Abstract: In order to reduce animal testing, companies registering chemical substances under the EU REACH legislation must propose rather than conduct certain tests on animals. Third parties can submit 'scientifically valid information' relevant to these proposals to the Agency responsible, the European Chemicals Agency (ECHA), who are obliged to take the information into account. The European Coalition to End Animal Experiments (ECEAE) provided comments on nearly half of the 817 proposals for vertebrate tests on 480 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…
that encourage the use of alternative test methods for hazard and risk assessment applications, such as read-across, prioritization, and screening (ECHA, 2016; US EPA, 2018;Taylor et al, 2014). Novel analytical and in vitro data, now commonly referred to as new approach methodologies (NAMs), are being used in support of regulatory decisions (Kavlock et al, 2018;Paul Friedman et al, 2020); however, concerns about the limitations of NAMs in decision-making also have been voiced (Gocht et al, 2015;Berggren et al, 2015).
…”
mentioning
confidence: 99%
“…
that encourage the use of alternative test methods for hazard and risk assessment applications, such as read-across, prioritization, and screening (ECHA, 2016; US EPA, 2018;Taylor et al, 2014). Novel analytical and in vitro data, now commonly referred to as new approach methodologies (NAMs), are being used in support of regulatory decisions (Kavlock et al, 2018;Paul Friedman et al, 2020); however, concerns about the limitations of NAMs in decision-making also have been voiced (Gocht et al, 2015;Berggren et al, 2015).
…”
mentioning
confidence: 99%
“…64 − Laboratory capacity in Europe has been reached, explaining the astonishingly stable numbers, and additional testing has been exported to other countries, especially China and India, and is thus not accounted for in the statistics. − A lot of testing is still to come: This holds true as completeness checks by ECHA, which shall be launched only in April 2020 65 , and the majority of accepted testing proposals (Taylor et al, 2014) have yet to be executed. Our own analysis of the testing proposals for developmental and reproductive toxicology for the first deadline alone (Rovida et al, 2011) suggested up to 1.6 million animals just for these endpoints.…”
Section: Genetically Altered Animalsmentioning
confidence: 99%
“…A further specification is given in Article 13, paragraph 1: In particular for human toxicity, information shall be generated whenever possible by means other than vertebrate animal tests, through the use of alternative methods… But, in reality, the application of the REACH Regulation has been disappointing. The European Chemicals Agency (ECHA) is very conservative when it comes to accepting the use of alternative methods by applicants, and it often demands that animal tests are conducted instead (43). To date, about 400 animal tests have been performed, without going through the proper consultation process (44).…”
Section: The Eu Reach Regulationmentioning
confidence: 99%
“…As a result, the 2014 ECHA report shows that, since 2009, more animal Including comprehensive lists of requirements to be fulfilled and functions to be performed tests than in vitro tests were carried out in experimental studies (Figure 6). The almost 5,000 animal tests mentioned had doubled since the last report of 2011, and it represents the use of a total of at least 700,000 animals (43).…”
Section: The Eu Reach Regulationmentioning
confidence: 99%